(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
In modern linguistics, the concept of "concept" is one of the central terms that reveal the connection between language and thinking. A person expresses his worldview, feelings and experiences in language. Therefore, language is studied not only as a means of communication, but also as a phenomenon that expresses culture, values and mentality. In linguistics, the concept of concept is at the heart of this process, because it is reflected through words, but contains a meaning that is broader than the word itself.